Centuries Encircle Me with Fire Selected Poems of Osip Mandelstam. a Bilingual English-Russian Edition. - Mandelstam, Osip (Academic Studies Press, 2022)
The introduction and translated poems of Mandelstam within are the gold-standard for critics and readers who don't know Russian. They expertly illuminate other Mandelstam translations, not replacing them, but rather allowing for a better understanding of what they specifically contribute.